The Challenge of Violent Drug-Trafficking Organizations An Assessment of Mexican Security Based on Existing RAND Research on Urban Unrest, Insurgency, and Defense-Sector Reform - Paul, Christopher (RAND Corporation, 2011)
A RAND team conducted a Delphi expert elicitation exercise, the results of which offer an assessment of the contemporary security situation in Mexico through the lens of existing RAND research on urban instability and unrest, historical insurgencies, and defense-sector reform. Assessment scorecards from these projects were used to obtain input from the expert panel and to guide the resulting discussion.